Análise dos estabelecimentos farmacêuticos de dispensação em Teresina-PI: da distribuição espacial aos indicadores de qualidade - Aragão, Alex Ferreira (2016)
According to the National Agency of Sanitary Vigilance - ANVISA, pharmaceutical establishment is the unit of public or private company for trade, sale, supply, transportation, storage, dispensing and distribution of drugs, medicines, pharmaceutical and related products. It must have characteristics of health service and obey rules that distinguish them from other commercial establishments. This study aimed to evaluate the pharmaceutical market in Teresina-Pi from pharmaceutical establishments profile study (includIng small pharmacies and drugstores and big retail companies). The work was divided into three parts which generated three chapters. First was made a study of local distribution of pharmacies / drugstores using georeferencing as a tool to better observe. In the second part aimed to outline the characteristics of dispensing establishments from Teresina city, Piauí. THE local distribution of pharmacies / drugstores and types (big or independent companies), operation, amount of technical managers and turnover of pharmacists. In third and last time it was made an assessment of good pharmaceutical practice in pharmacies / large and small drugstores in the city of Teresina - PI. At the end, the profile of pharmacies in Teresina-PI was characterized by having 229 pharmacies / drugstores (between small and large), the pharmacy / drugstore chain have better conditions but infrastructure as well as of small, and few makes pharmaceutical care services. It was observed that the geoprocessing tool can be a great ally in studies of use / consumption of drugs and that, among the pharmaceutical establishments of Teresina, large ones are closer to the fulfillment of legal requirements and even these do not have attention pharmaceutical deployed.